El dibujo como expresión de la forma (2020)
In this essay, the author analyzes the concept of Form in design from the perspective of technical drawing. This standpoint is one of the main objects of study in this discipline, which, in addition, acts as an essential means for the effective communication of design projects. In order to illustrate the concept of Form, the author presents a historical view from the beginnings of geometry to the most important representatives of projection methods used now, taking into account the contribution of nature to the obtaining of special shapes that offer designers a wide range of possibilities for the definition of projects through drawings.